ÉPOCAS DE APLICAÇÃO DE REGULADOR DE CRESCIMENTO E DE SOMBREAMENTO ARTIFICIAL AFETANDO CULTIVARES DE TRIGO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
The use of the growth regulator trinexapac-ethyl aims to reduce height of wheat plants avoiding lodging and losses caused by it. In addition, causes changes leaf architecture the plant have a better utilization of solar radiation. With the aim to evaluate the effects of application times of the growth regulator trinexapac-ethyl with or without artificial shade at different growth stages of wheat, two experiments were carried out in the Farm School of State University of Ponta Grossa, in the municipality of Ponta Grossa, Parana, two in 2010 and one in 2011. The experimental design was the randomized blocks with four replications in a factorial design, in 2010 was 4 x 3 (times of application of trinexapac-ethyl x time shading) in wheat cultivars Quartzo and Supera in 2011 in schedule 4 x 4 (time of application of trinexapac-ethyl x time shading), the cultivar Quartzo. Treatments consisted of four periods of application of trinexapac-ethyl (without application, tillering, between first and second perceivable knot and between second and third perceivable knot) at a dose of 100 g ha-1 in both the years and four seasons of shading (without coverage, the booting stage to silking + 15 days (x), X + 15 days) in the year 2011 three times (without coverage, the silking + 15 days (x) and X + 15 days) in 2010. No interaction was observed between treatments for the evaluated characteristics. In both trials no differences were observed for stem diameter, leaf area and harvest index. The shade did not affect the number of spikes per meter, grains per spikelet, number of tillers per plant in two years and the lowest grain yield occurred when the shading was done at the end of anthesis and grain filling (X + 15). The number of spikelets per spike was not affected by shading in the 2010 harvest, but the 2011 the period of shading done at the end of silking + 15 days increased the number of spikelets. The trinexapac-ethyl did not affect most of the yield components evaluated. Shading not affect the plant height. In the 2011 harvest, with the application of growth regulator between the first and second knot and between the second and third knot visible to the plant height was lower. The yield was not affected by timing of application of trinexapac-ethyl. In the 2011 harvest shading done at the end of anthesis and grain filling (X + 15 days) resulted in lower productivity.
Keywords: Triticum aestivum; trinexapac-ethyl; sombreamento; Triticum aestivum; trinexapac-ethyl; shading; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA